Analysis of Public Transportation (Bus) Demand on the Pontianak-Aruk Route - Salsabila, Nur Aulia; Mukti, Elsa Tri; Mayuni, Siti (Jurnal Teknik Sipil, 2025)
The Pontianak–Aruk bus route serves a strategic role in supporting accessibility and mobility in Sambas Regency, particularly in connecting to the Aruk Border Crossing Post (PLBN). The growing population and increasing tourism activity have heightened the demand for safe, affordable, and efficient public transportation. This study analyzes passenger characteristics, estimates Vehicle Operating Costs (VOC), and determines the optimal fleet size. Primary data were collected through observations, interviews, and surveys conducted at the Pontianak and Aruk terminals over three days, while secondary data were obtained from relevant agencies. Using a descriptive quantitative approach, the analysis included load factor, VOC, and fleet requirements based on the break-even point. Results show that most passengers are aged 21–30 years, traveling mainly for homecoming, with affordability as the key factor in choosing buses. The average load factor was 0.63, with 28 passengers per trip; however, headways were irregular and fell below service standards. Operating costs totaled IDR 592,358,000 per year, and the optimal fleet size was determined to be three units, compared to the existing four. These findings suggest the need for fleet adjustment to enhance efficiency and service quality in cross-border public transport.